Hemocompatibility of cellulose phosphate aerogel membranes with potential use in bone tissue engineering - Schimper, Christian B.; Pachschwöll, Paul; Maitz, Manfred F.; Werner, Carsten; Rosenau, Thomas; Liebner, Falk (Frontiers in Bioengineering and Biotechnology, 2023)
Cellulose is an appealing material for tissue engineering. In an attempt to overcome some obstacles with cellulose II cell scaffolding materials related to insufficient biomineralization, lack of micron-size porosity, and deficiency in electrical surface charge, respective solutions have been proposed. These included covalent phosphorylation of different cellulose source materials targeting relatively low degrees of substitution (DS 0.18-0.23) and processing these cellulose derivatives into scaffolding materials by a dissolution/coagulation approach employing the hitherto rarely used TBAF/DMSO/H2O system for cellulose dissolution. Here, we report bioactivity and preliminary hemocompatibility testing of dual-porous cellulose phosphate aerogels (contrasted with the phosphate-free reference) obtained via coagulation (water/ethanol), solvent exchange and scCO2 drying. Deposition of hydroxyapatite from simulated body fluid (7 days of immersion) revealed good bioactivity (1.5-2.2 mg Ca2+ per mg scaffold). Incubation of the scCO2-dried and rehydrated scaffolding materials in heparin anticoagulated human whole blood was conducted to study selected parameters of hemostasis (prothrombin F1+2 fragment, PF4, count of thrombocyte-leukocyte conjugates) and inflammatory response (C5a fragment, leukocyte activation marker CD11b). Adhesion of leukocytes on the surface of the incubated substrates was assessed by scanning electron and fluorescence microscopy (DAPI staining). The results suggest that phosphorylation at low DS does not increase platelet activation. However, a significant increase in platelet activation and thrombin formation was observed after a certain fraction of the negative surface charges had been compensated by Ca2+ ions. The combination of both phosphorylation and calcification turned out to be a potent means for controlling the inflammatory response, which was close to base-line level for some of the studied samples.